PENGEMBANGAN BUDIDAYA UDANG WINDU DENGAN SISTIM MODULAR DI TAMBAK - Nur Ansari Rangka (Berkala Perikanan Terubuk, 2011)
Transferring periodically of rearing shrimp between plots of land, anaquaculture technology to increase productivity of shrimp pond, was calledmodular system. The research was applied on 15 pond with 250 m2 of each thatwas separated on 3 category including A, B and C categories. 4, 6 and 8 larva/m2(PL40) was distributed on each of A, B and C category. During 90 rearing days,the larvae were supplied by means of production such as dolomite, organicmanure of chicken fesses and pathogen/pest control (saponim). The B – categoryshowed the highest average product of 19,36 kg/plot while C – category of 16,69kg/plot and A – category of 15,73 kg/plot. While the best production was shownby A- category, 4 larva/m2 , with total average product was 15,73 kg/ 250 m2 if theproduction conversed to 1 ha, the highest product is in A- category/treatment (4larva/m2), with average benefit cost is Rp. 21.494.250,- per season . B/C ratioanalysis shows point number higher than 1, which indicated that the aquaculturewith modular system is potential to implement. Suggested that larva content onaquaculture activities of tiger prawn in brackish ponds without water wheel(kincir) is 4 larva/m2.